Keselamatan Kerja pada Petugas Perawatan Body Kereta Api di Balai Yasa Manggarai - Atik Siti Kuswati; Erifendi Churniawan; Farid Hafifuddin Huda (Syntax Idea)
The Technical Implementation Unit of Balai Yasa Manggarai is an organizational unit within PT. Kereta Api Indonesia (Persero) under the Directorate of Facilities (D4), located in Manggarai, Tebet District, South Jakarta, the Special Capital Region of Jakarta. Balai Yasa Manggarai is the sole maintenance facility in the Jabodetabek area capable of accommodating approximately 200 railway cars for various levels of maintenance, including light maintenance, final maintenance, and modifications. Maintenance activities at Balai Yasa Manggarai cover passenger cars, dining cars, power cars, and baggage cars. The maintenance facility consists of four departments: the electrical department, the rolling stock department, the bogie department, and the metal department. The purpose of maintaining railway car bodies at Balai Yasa Manggarai is to ensure the reliability of railway equipment during operations. However, there are potential hazards and risks associated with railway car body maintenance that can result in minor to severe injuries to the personnel. This research aims to identify potential hazards and risks in railway car body maintenance activities as a preventive measure to avoid workplace accidents in the future. The study uses a qualitative descriptive method. The population in this research includes all personnel involved in railway car body maintenance at Balai Yasa Manggarai. The sampling technique employed is purposive sampling, with the criteria being individuals who participate in railway car body maintenance activities and have worked in the Railway Worker Category for more than 2 years at Balai Yasa Manggarai. Data collection methods include observation, interviews, and documentation. The analysis method involves hazards identification, risk assessment, and determining control measures (HIRADC). HIRADC is used to assess all potential hazards and risks to determine the risk level and control measures required. The research identified 17 hazards, including 5 with extreme risk, 4 with high risk, 7 with moderate risk, and 1 with low risk. Risk control measures involve engineering techniques, administrative procedures, and personal protective equipment (PPE).